2021
DOI: 10.1080/23311975.2021.1930870
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tax avoidance on the value of listed firms in Vietnam

Abstract: The study aims to examine the impact of tax avoidance on the value of listed firms in Vietnam. Using a sample of 209 non-financial businesses listed on the Ho Chi Minh Stock Exchange (HOSE) in Vietnam for the period 2010-2018 and the Panel-Corrected Standard Errors (PCSE) to overcome the model's errors, we show that tax avoidance has a negative impact on the value of businesses at a 10% significance level. In addition, other variables, such as foreign ownership, investment, return on assets, leverage, the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 21 publications
(46 reference statements)
2
14
1
10
Order By: Relevance
“…This finding is consistent with Mandacı and Gumus (2010) who explain that too much managerial ownership could potentially lead managers to be more concerned about their own interests and the firm value decrease. However, the firm size has a positive impact on the firm value, which is in accordance with the outcomes of Minh Ha et al (2021) in Vietnam and Assidi et al (2016) and Nafti et al (2020) in Tunisia. The leverage has a negative effect on this value.…”
Section: Correlation Matrixsupporting
confidence: 81%
See 2 more Smart Citations
“…This finding is consistent with Mandacı and Gumus (2010) who explain that too much managerial ownership could potentially lead managers to be more concerned about their own interests and the firm value decrease. However, the firm size has a positive impact on the firm value, which is in accordance with the outcomes of Minh Ha et al (2021) in Vietnam and Assidi et al (2016) and Nafti et al (2020) in Tunisia. The leverage has a negative effect on this value.…”
Section: Correlation Matrixsupporting
confidence: 81%
“…They have recently reported that the tax planning activity, as measured by the proxies based on reported accounting information, has a negative impact on the firm value. Minh Ha et al. (2021) also denote a negative effect of tax avoidance on the value of listed firms in Vietnam for the period of 2010–2018.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the tax avoidance strategy helps companies to have higher free cash in hand by transferring the cash from the government to the shareholders which then should increase the wealth and companies' performance (Khuong et al, 2020). The tax avoidance strategy is used by the company to finance the company activities and cover the liabilities, thereby increasing the company's performance and value (Minh Ha et al, 2021).…”
Section: Tax Avoidance and Companies' Performancementioning
confidence: 99%
“…According to Desai & Dharmapala (2009), the concept of tax avoidance, when viewed through the lens of agency theory, results in higher agency costs and an increase in the number of tools managers use to participate in predatory behaviour. From another perspective, tax avoidance is a strategy that allows businesses to have more free cash in hand by transferring funds from the government to companies (Khuong et al, 2020), which at the same time helps businesses finance their operations and pay off debt; hence, improving their performance (Minh Ha et al, 2021). As a result of the various instructions and controls over management and political opportunism, there is no definitive outcome of tax avoidance effect on companies' performance.…”
Section: The Role Of Political Connection On Tax Avoidance and Perfor...mentioning
confidence: 99%